Examining the Impact of Organizational Culture on Teachers' Loyalty in Vocational High Schools - Umi Anugerah Izzati, Warih Handayaningrum, Olievia Prabandini Mulyana (South Eastern European Journal of Public Health, 2025)
Introduction: Every educational institution has goals to achieve. One way to achieve the goal is if the teachers have loyalty to the school. There are various factors that influence teacher loyalty, one of which is organizational culture. Objectives: The purpose of this study is to determine the influence of organizational culture on the loyalty of vocational school teachers. Methods: Quantitative techniques with a non-experimental design were used to analyze data on questionnaires with a total of 154 vocational high school teachers as subjects. Data analysis used a simple regression analysis test with SPSS software. This research instrument uses a psychological scale developed by the research team based on the theory of organizational culture and loyalty. Results: The research results show that there is a relationship between organizational culture and teacher loyalty with a correlation coefficient of 0.759 and a significance value of 0.000. This means that if the organizational culture score increases, the loyalty score will also increase. Conclusions: The results of this study are expected to be able to provide considerations for schools to develop strategies to increase the loyalty of teachers. In addition, it can also pay attention to other factors besides organizational culture that can affect teacher loyalty.